Improving students' achievement in learning English through learning outdoor method in SMA 1 Bone - Sintia Pakaya; Marina Pakaja (Journal of English Teaching and Linguistic Issues (JETLI), 2022)
This research aims to determine the improvement of students' English learning achievement through the outdoor learning method. The research was conducted on 16 students of class X, SMAN 1 Bone. This research applied classroom action research in which the data collection techniques were carried out using tests and student observation sheets. The results indicated that the use of learning outdoor method has increased the students' English achievement. This can be seen from the analysis result of prior observation data at the pre-action stage where students who completed the minimum completeness criteria (KKM) were 55.1%. Then cycle I was administered where students who achieved the minimum completeness criteria (KKM) were 56.25%, and cycle II of students who achieved the minimum completeness criteria (KKM) has increased to 87.5%.